An Error Analysis on the Use of English made by Local Tourism Workers of Jatiluwih Tourism Destination at Tabanan Bali - Ni Luh Putu Sri Widhiastuty; I Ketut Murdana (LACULTOUR: Journal of Language and Cultural Tourism, 2022)
The research in general aimed on analyzing English language errors made by local tourism workers of Jatiluwih tourism destination in Tabanan, Bali, and specifically it aimed in revealing and analyzing types of errors made by the local tourism workers of Jatiluwih Tourism Destination in using English with foreign tourists. The primary research data are directly collected from the English language expressions used by the local tourism workers as informan of Jatiluwih Tourism Destination during their communication activities with the foreign tourists. The data informan are selected using purposive, snowball and abundant sampling techniques with the total number of 30 samples of the local tourism workers of Jatiluwih Tourism Destination in Tabanan, Bali. The collected data are analyzed using Error Analysis Theory proposed by Tarigan (1985) and Ellis (1986) (cited in Tarigan and Tarigan, 2011:63-64). The research reveal that the English language errors committed by local tourism workers of Jatiluwih Tourism Destination i Tabanan, Bali can be categorized into two major errors, which are: (1) errors of linguistic taxonomy category, which consists of two errors types, such as : (a) morphology errors and, (b) syntactic errors; (2) Errors of surface strategy taxonomy.